The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1055/s-0038-1654720
|View full text |Cite
|
Sign up to set email alerts
|

Lemierre Syndrome: Clinical Update and Protocol for a Systematic Review and Individual Patient Data Meta-analysis

Abstract: Lemierre syndrome usually affects otherwise healthy adolescents or young adults and occurs at an overall rate of 1 to 10 cases per million person-years with an estimated fatality rate of 4 to 9%. Diagnostic criteria remain debated and include acute neck/head bacterial infection (often tonsillitis caused by anaerobes at high potential for sepsis and vascular invasion, notably Fusobacterium necrophorum) complicated by local vein thrombosis, usually involving the internal jugular vein, and systemic septic embolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 62 publications
(60 reference statements)
0
53
0
6
Order By: Relevance
“…4 The use of anticoagulants, particularly as low-molecular-weight heparin, is still under debate. 4,5 To date, only one group is working on a systematic review and meta-analysis to clarify the treatment of the complication of Lemierre's syndrome. 5 Since the condition appears to be underreported and not properly highlighted, an eventual systematic review and meta-analysis of the occurrence of the Lemierre's syndrome is highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…4 The use of anticoagulants, particularly as low-molecular-weight heparin, is still under debate. 4,5 To date, only one group is working on a systematic review and meta-analysis to clarify the treatment of the complication of Lemierre's syndrome. 5 Since the condition appears to be underreported and not properly highlighted, an eventual systematic review and meta-analysis of the occurrence of the Lemierre's syndrome is highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…89% of patients are between the ages of 10-35 years [4]. Despite its rarity, clinical experience suggests that its incidence may be on the rise, possibly secondary to antibiotic resistance, changes in prescription patterns, or the increased efficiency of diagnostic technologies [5].…”
Section: Discussionmentioning
confidence: 99%
“…Prompt institution of anticoagulation may prevent thrombotic extension, embolization, and new thromboembolic events but may also expose patients to bleeding complications. It is also unclear whether anticoagulation may facilitate spread of septic material or result in a hemorrhagic transformation of embolic lesions [5]. When deciding on anticoagulation, the medical team must carefully consider the patients characteristics, severity of disease, bleeding risk, and risk of new thromboembolic complications as well as the drugs pharmacokinetics [5].…”
Section: Discussionmentioning
confidence: 99%
“…The early notion that the typical primary infection was a tonsillitis and the thrombus was usually located in the internal jugular vein initially suggested that bacteria spread through the tonsillar and peritonsillar veins [6]. As it became clear that other head or neck infections can cause the syndrome and that other vessels, including the external jugular vein or the facial vein, may be involved, other pathways were postulated, including direct extension through the fascial plane between the tonsils and the parapharyngeal space and lymphatic spread [7]. All reports from the twentieth century confirmed the syndrome's specific association with Fusobacterium necrophorum.…”
Section: Definition Physiopathology and Epidemiologymentioning
confidence: 99%
“…is not considered to be mandatory: this organism is difficult to isolate, cultures may be negative due to empiric antibiotic therapy, and other bacteria seem able to cause Lemierre syndrome [5,17]. In a recent analysis of 712 cases reported in the scientific and grey literature since 2000, which were identified using the commonly applied broad definition [7], the cases satisfying the "typical" definition (oropharyngeal infection and isolation of Fusobacterium spp.) only represented approximately half of the observed spectrum of the syndrome; Fig.…”
Section: Definition Physiopathology and Epidemiologymentioning
confidence: 99%